Antimalarial activity of ethyl acetate extract of Garcinia dulcis kurz stem bark - Gunawan Pamudji Widodo; Mamik Ponco Rahayu (Indonesian Journal of Pharmacy, 2010)
In-vivo antimalarial activity of ethyl acetate extract of Garcinia dulcis Kurz stem  bark  have  been  evaluated  against  Plasmodium  berghei  induced  mice. Antimalarial  test  was  conducted  by  paracitemia  investigation  and  leucocyte counting  of  paracite  induced  mice  blood,  after  oral  administration  of  Garcinia dulcis  stem  bark  extract  dose  of  25  mg,  50  mg,  as  well  as  75  mg/kg  bw.  The highest  antiplasmodial  activity  and  decresing  of  leucocyte  amount  was  showedby  extract  of  dose  of  50  mg/kg  bw.  The  compounds  identified  in  ethyl  acetate extract  of  Garcinia  dulcis  stem  bark  were  flavonoid,  saponin  and  tannin.  The compounds that have antimalarial activity weren’t yet known.Keywords: antimalarial, Garcinia dulcis Kurz, stem bark, paracitemia